An investigation on compatibility of experimental effective atomic numbers of some Fe-Ni alloys with those predicted by MCNP - Kalecik, Sedanur; Yilmaz, Demet; Kurucu, Yakup; Gurol, Ali; Toker, Ozan; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this work, effective atomic numbers of some Fe-Ni alloys were obtained experimentally by coherent and Compton scattering intensity ratios at scattering angle of 168 degrees by using Americium-241 gamma rays (59.54 keV) and High Purity Germanium Detector (HPGe) detector. The experimental setup consisting of Am-241 and HPGe detector was simulated using the MCNP (Version 6.2) code. The intensity ratios of coherent and Compton scattering peaks of Cr, Mn, Fe, Co, Ni, Cu and Zn elements used for calibration were plotted as a function of their atomic numbers. The effective atomic numbers of the investigated alloys were determined by the interpolation method based on the coherent to Compton scattering ratio. Coherent to Compton intensity ratios of the alloys ranged from 1098.02 to 1165.47. The effective atomic number values obtained by MCNP simulation of the alloys were between 26.423 and 27.211, the experimentally effective atomic number values were between 26.524 and 27.382, and the theoretical effective atomic number values obtained with ZXCom were between 26.710 and 27.594. It is observed that the results obtained by the simulation method are in agreement with the experimental results and the theoretical results obtained with ZXCOM.
Keywords: Alloy; Effective atomic number; Coherent scattering; Compton scattering; MCNP; X-RAY; COMPTON RATIO; RAYLEIGH; RADIATION; Chemistry; Nuclear Science & Technology; Physics